Further insights into calcium sulfoaluminate cement expansion. Issue 4 (31st October 2018) - Hargis, Craig W.; Lothenbach, Barbara; Müller, Christian J.; Winnefeld, Frank
Abstract : There is still an ongoing debate on the mechanisms of expansion of calcium sulfoaluminate (CSA) cements, which can be either favourable, for example, in shrinkage compensating construction materials, or deleterious in cases of excessive expansion. In order to expand on previous studies, CSA cements with molar ratios ( M ) of calcium sulfate/ye'elimite of 0·1, 1, 1·5 and 2 were investigated from 30 min to 182 d. All systems showed expansion, and expansion was found to increase with increasing gypsum content. The sample with M = 2 showed a high expansion and severe cracking after 1 d of hydration. Based on the pore solution chemistry, crystallisation pressures were calculated, which revealed that not only ettringite, but also the other hydrate phases present (aluminium hydroxide (AH3 ), strätlingite, calcium aluminate decahydrate (CAH10 ), monosulfate) may contribute to the total crystallisation pressure. The percolation pore radii obtained by mercury intrusion porosimetry were used to calculate hydrostatic tensile stresses. It was found that in all investigated systems the hydrostatic tensile stresses exceeded the 1 d tensile strength, which is in line with the fact that all samples showed expansion.